2019
DOI: 10.3168/jds.2018-14966
|View full text |Cite
|
Sign up to set email alerts
|

Production of recycled manure solids for bedding in Canadian dairy farms: I. Solid–liquid separation

Abstract: Canadian dairy producers have an increasing interest in recycled manure solids (RMS) as bedding material because of reduced availability of traditional bedding resources. Information regarding methods to obtain RMS and composition of RMS is very limited. Hence, a 2-part investigation was developed to compare the performances of 3 mechanical solid-liquid manure separators (part I) and 4 composting methods (part II; companion paper in this issue) for the production of high quality RMS. In this first study, a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Indeed, some studies indicated a high quantity of Streptococcus spp. in RMS [e.g., 9 (Sorter et al, 2014) and 6 log cfu/g of DM (Fournel et al, 2019b)]. Fournel et al (2019b) demonstrated that solid-liquid separation methods and composting time did not affect their number in RMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some studies indicated a high quantity of Streptococcus spp. in RMS [e.g., 9 (Sorter et al, 2014) and 6 log cfu/g of DM (Fournel et al, 2019b)]. Fournel et al (2019b) demonstrated that solid-liquid separation methods and composting time did not affect their number in RMS.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic digestion is used instead of or as well as composting, commonly in the United States (Leach et al, 2015). A lot of potential benefits are associated with RMS, such as cost savings, availability, and cow comfort (Bradley et al, 2014;Fournel et al, 2019b). Also, this type of bedding can be considered as a strategy to mitigate pollution from livestock manure management (Petersen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some form of manure treatment to concentrate the nutrients can significantly reduce the transportation costs and creates the opportunity for altering the balance of nutrients in fractions of the treated manure to meet different crop production requirements (Withers et al, 2015). The simplest form of treatment, with the lowest capital cost, is to separate the solid from the liquid portion of the manure (Burton, 2007; Fournel et al, 2019). The majority of the P remains with the solid fraction (Rico et al, 2012), which can then be transported off‐farm to be used in areas that need P. The remaining liquid retains a high proportion of ammonium N, so it can be used for crops with a high N demand that are growing on soils that already have adequate P. Some dairy operations are further composting the solids portion and reusing it as bedding materials for the cows (Fournel et al, 2019; Husfeldt et al, 2012); the use of this composted material has been well documented from the perspective of herd health but not regarding the potential for P concentrations to build up in the bedding material as it is reused over multiple cycles.…”
Section: Options For Mitigating Phosphorus Imbalancesmentioning
confidence: 99%
“…The Table 1. Bacterial counts in composted recycled manure solids (RMS) using static windrows (SW), turned windrows (TW), or a drum composter (DC) in original 1 and converted units Item Harrison et al (2008) Timms 2008 Screen-separated RMS composted in windrows outside for 2 wk and turned every few days (30.0% DM and density assumed at 300 kg/m 3 based on part I (Fournel et al, 2019) results at this DM content).…”
Section: Experimental Designmentioning
confidence: 99%
“…Physical (bulk density, water absorption, porosity, and particle size distribution), chemical [pH, DM, ash, OM, C, total Kjeldahl N (TKN), NH 4 -N, and organic N], and bacteriological (Escherichia coli, Klebsiella spp., Staphylococcus spp., Streptococcus spp., and Enterococcus spp.) analyses were performed following the methods presented in Table 1 of the companion paper (Fournel et al, 2019).…”
Section: Data Collectionmentioning
confidence: 99%